Financial Technology and its impact on Banking Financial Performance in Indonesia - Anggya Sophia Imannisa; Ghazali Syamni; Jummaini Jummaini; Husaini Husaini; Rico Nur Ilham; Darmawati Muchtar Muchtar (Program Studi Keuangan & Perbankan, Fakultas Ekonomi dan Bisnis, Universitas Komputer Indonesia, 2025)
Return on Assets (ROA), the main measure of profitability, is used in this study to investigate how the use of financial technology affects the financial performance of Indonesian banking institutions. Four Fintech variables—the Quick Response Code Indonesian Standard (QRIS), ATMs, internet banking, and mobile banking—were examined. Ten commercial banks' secondary data for the 2022–2024 timeframe were used quantitatively using panel data regression, combining cross-sectional and time series dimensions. With statistical inference utilizing the F-test, t-test, and coefficient of determination, the Fixed Effect Model (FEM) was selected as the most suitable model based on the Chow and Hausman tests. The findings demonstrate that ROA is significantly and negatively impacted by mobile banking, whereas internet banking and QRIS have positive and significant effects. ATM usage was found to be insignificant. Overall, Fintech adoption positively influences financial performance, highlighting the need for effective strategies to maximize technological benefits while managing operational costs. Keywords: financial; technology; performance; banks; Indonesia